A cross sectional study on depression among elderly people living in old age homes in Kurnool city - Bathala, Persis S.; Sayolu, Cynthia S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Aging is a normal process, which is associated with physical, social and psychological changes. Depression among elderly is an important public health problem responsible for considerable morbidity and disability. Hence this study was undertaken to estimate the prevalence of depression among inmates of old age homes. The main was to know the prevalence and level of depression and to assess socio demographic factors associated with depression among inmates of old age homes. Methods: A cross sectional study was done from August 2019 to October 2019 in old age homes of Kurnool city with a sample size of 60 by simple random sampling. Depression was assessed using geriatric depression scale. Data entered in MS Excel version 7 and analysed by SPSS version 21. Chi-square test was applied to test the significance and p value less than 0.05 was considered as statistically significant. Results: The overall prevalence of depression was found to be 66.7% among inmates and is positively associated with female sex, increasing age, illiteracy, low socio economic status economical dependency and dependency for daily activities. Conclusions: As the prevalence of depression is more among inmates there is a need to provide emotional support and facilities to engage them in various social activities of the community especially the elder females to prevent them from being depressed.